2001
DOI: 10.1093/emboj/20.10.2487
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase PKR is required for platelet-derived growth factor signaling of c-fos gene expression via Erks and Stat3

Abstract: The double‐stranded RNA (dsRNA)‐activated protein kinase PKR is an interferon (IFN)‐induced enzyme that controls protein synthesis through phosphorylation of eukaryotic initiation factor 2α (eIF‐2α). PKR also regulates signals initiated by diverse stimuli, including dsRNA, IFN‐γ, tumor necrosis factor‐α, interleukin‐1 and lipopolysaccharide, to different transcription factors, resulting in pro‐inflammatory gene expression. Stat3 plays an essential role in promoting cell survival and proliferation by different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 73 publications
1
54
0
Order By: Relevance
“…For instance, PKR mediates heparin-induced SMC antiproliferation through the regulation of STAT1 (10). However, further studies have shown a more complex function in cell proliferation (6,26). Besides the PKR-mediated proproliferation function of TNF, it may also play an important role in platelet-derived growth factor-induced cell proliferation via a different pathway.…”
Section: E521mentioning
confidence: 99%
“…For instance, PKR mediates heparin-induced SMC antiproliferation through the regulation of STAT1 (10). However, further studies have shown a more complex function in cell proliferation (6,26). Besides the PKR-mediated proproliferation function of TNF, it may also play an important role in platelet-derived growth factor-induced cell proliferation via a different pathway.…”
Section: E521mentioning
confidence: 99%
“…These PKR Ϫ/Ϫ mice do not exhibit growth abnormalities or increased tumorigenesis (20) and, in contrast to Stat1 knock-out mice (3, 4), do not display significant susceptibility to most viral infections (20). In the case of Stat3, previous data provided evidence for a positive role of PKR in Stat3 activation in platelet-derived growth factor-treated cells (42). However, this regulation was described in MEFs from a PKR Ϫ/Ϫ mouse lacking the N-terminal domain of the kinase (43).…”
Section: Discussionmentioning
confidence: 93%
“…It has been proposed that PKR mediates apoptosis at the transcriptional level. For example, PKR signals through STAT1 and STAT3 (36,43,44), interferon regulatory factor 1 (IRF1) (16,45), IRF3 (46), p53 (17,47,48), and the IKK complex to regulate transcription during proinflammatory (16,17,40,45) and/or proapoptotic responses (12,40,45,49). PKR-dependent apoptosis was also associated with Fas-associated death domain (FADD)-mediated activation of caspase 8 (50,51) and up-regulation of Fas and Bax (18,52,53).…”
Section: Discussionmentioning
confidence: 99%